2015
DOI: 10.1177/0268580915605650
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance footage and space segregation in Mexico City

Abstract: This study discusses police use of surveillance footage to solve crimes in urban locations and in marginalized neighborhoods, and in particular explores how surveillance cameras and the quality of video they produce result in differential displays of crime. Videos of young people being kidnapped in downtown Mexico City reveal that surveillance systems in marginalized areas are of consistently poor definition and clarity, which contrasts sharply with the clear and distinct images produced by video surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Low levels of physical activity were also found among children in lower socio-economic status groups in South Africa, highlighting the increased risk to obesity many children in low socio-economic groups in developing countries face (McVeigh et al, 2004). These findings also indicate wider social problems in Mexico such as public insecurity, crime and corruption, which make public spaces in low-income areas unsafe and perpetuate social inequalities (Arteaga Botello, 2015). Similar to Jennings-Aburto et al (2009) research on physical education in public schools in Mexico City, this study also revealed that physical education is insufficient in public schools and it is recommended that the quantity and quality of physical education be increased.…”
Section: Discussionmentioning
confidence: 97%
“…Low levels of physical activity were also found among children in lower socio-economic status groups in South Africa, highlighting the increased risk to obesity many children in low socio-economic groups in developing countries face (McVeigh et al, 2004). These findings also indicate wider social problems in Mexico such as public insecurity, crime and corruption, which make public spaces in low-income areas unsafe and perpetuate social inequalities (Arteaga Botello, 2015). Similar to Jennings-Aburto et al (2009) research on physical education in public schools in Mexico City, this study also revealed that physical education is insufficient in public schools and it is recommended that the quantity and quality of physical education be increased.…”
Section: Discussionmentioning
confidence: 97%
“…Большинство современных исследований камер посвящено критике массового распространения таких систем, либо, наоборот, изучению их эффективности, но не вопросу дизайна инфраструктур и их связи с мыслительными коллективами. В немногочисленных исключениях даются широкие выводы о том, что камеры могут располагаться как в центрах городов, так и на их окраинах [Arteaga Botello, 2015], в зажиточных или, наоборот, неблагополучных районах [ de Keersmaecker, Debailleul, 2016;Norris, Armstrong, 1999].…”
Section: безопасное/опасное различение и исследования инфраструктурunclassified